A new type of ECT stimuli: burst stimulus ECT - Aksay, Suna Su; Janke, Christoph; Sartorius, Alexander (Pharmacopsychiatry, 2015)
Objectives: Pulse width in electroconvulsive therapy has significant influence on effectiveness and side effects. While shorter pulses are beneficial for cognitive performance, there is still a debate about a negative impact on ECT efficacy at least for ultra-brief pulse durations. Methods: We report a first patient treated with burst stimulus ECT, i. e., with 4 consecutive 250-µs pulses, separated by another 250 µs. Within the same patient we compared 6 classical vs. 6 burst stimulus ECT sessions. Results: In all cases typical tonic-clonic seizure was observed. Seizure parameters like concordance, coherence and mid-ictal amplitude increased numerically, but not significantly with burst ECT. The time needed to show a reorientation was significantly shortened with burst stimuli (30 min vs. 14 min, p=0.007). Conclusions: In conclusion we present the first case of ECT in a single patient comparing “classical” single stimulus pulses vs. burst stimulus ECT. The new burst stimulus was better tolerated regarding reorientation time after the treatment, while parameters of seizure quality remained basically unchanged. Whether burst stimulus ECT has the potential to improve ECT quality by reducing side effects without losing efficacy has to be investigated in clinical trials.